SUSTAINABLE DIGITAL-BASED HUMAN RESOURCE CAPACITY MODEL DESIGN TOWARDS A BLUE ECONOMY TOURISM AREA IN TANJUNG WIDORO VILLAGE, MENGARE ISLAND, GRESIK REGENCY - Mujanah, Siti; UROHMAN, TAUFIQ; Ridwan, M. Sihab (Universitas Nahdlatul Ulama Surabaya, 2024)
The potential for blue economy tourism on Tanjung Widoro Village, Mengare Island, Gresik, East Java requires the support of competent human resources and community participation for management that supports economic improvement and environmental sustainability. This study aims to design a digital-based sustainable human resource capacity model using a qualitative approach with in-depth interviews. The research results show that the digital-based sustainable HR capacity model includes continuous training in technical, managerial and digital aspects, strengthening the organization through local leadership, collaborative work culture, functional organizational structure and fair incentives, institutional reform to move towards tourism villages, and use of digital technology for HR management and marketing. HR capacity development requires the support of local communities, government, business players and educational institutions. This approach is expected to create digital-based sustainable human resources that support tourism management without damaging marine ecosystems.